Teaching learning from the perspective of sociocultural constructivism (Revista Electrónica REDINE, 2018)
In the conception constructivista, the subject and the object join the process of construction of the knowledge, which, it stops being a linear representation of what happens in the reality, independently of the man who constructs it. The knowledge not only is determined by schemes and innate and / or acquired capacities, but the needs of self-organization and development of the own subjective system, in this respect, it enters game the sociocultural context where one is immersed.
Keywords: constructivist conception; self-organization; socio-cultural context